The Effectiveness of Targeted Shooting Exercises in Improving Kick Accuracy in Young Development Soccer Players - Irsyad Maulana; Martin Sudarmono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The main problem in this study is the low accuracy of players' kicks when in front of the goal. This study aims to test the effectiveness of  targeted  shooting exercises  in improving kick accuracy in Bina Muda football players. The research method used was a quasi-experiment with a pretest-posttest design of one group. The research sample amounted to 20 players taken using  the total sampling technique. The research instrument used kick accuracy tests carried out before and after the intervention. The results of the descriptive analysis showed a significant increase in the average shot accuracy score, from 2.65 during the pretest to 6.05 during the posttest. The study data showed that they were normally distributed (p > 0.05) and had homogeneous variance (p = 0.864). Based on the hypothesis test using  the Paired Sample T-Test, a t-count value of -11.855 was obtained with a significance of 0.000 < 0.05. These findings suggest that there is a very significant difference between the ability of the kick to be accurate before and after treatment. The decrease in standard deviation from 1,631 to 1,572 also indicates that the player's abilities have become more consistent collectively. The conclusion of this study is that  targeted shooting  exercises  are highly effective in improving the kick accuracy of Young Builders players through the formation of muscle memory and sharper visual focus.